2006
DOI: 10.1093/carcin/bgi370
|View full text |Cite
|
Sign up to set email alerts
|

Genistein stimulates growth of human breast cancer cells in a novel, postmenopausal animal model, with low plasma estradiol concentrations

Abstract: We have demonstrated that genistein (GEN) stimulates growth of estrogen-dependent breast tumors in vivo. In this study, we evaluated whether dietary GEN can act in an additive manner with low circulating levels of 17beta-estradiol (E2). We developed an E2 delivery system using silastic implants that yield low circulating plasma E2 levels similar to those observed in postmenopausal women. We inserted various concentrations of E2 silastic implants (1:127, 1:63, 1:31, 1:15 and 1:7 = E2:cholesterol) and injected e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 67 publications
4
73
0
Order By: Relevance
“…Phytoestrogens including genistein were originally thought to contribute to the decreased breast cancer risk associated with Asian women on high-soy diets compared with American women. However, recent animal, clinical, and gene expression studies provide evidence against its preventive role in breast cancer (32,33). Our BRET assay shows that genistein induces ER␣ homodimerization at 100 nM, a physiological concentration easily achievable by dietary intake (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytoestrogens including genistein were originally thought to contribute to the decreased breast cancer risk associated with Asian women on high-soy diets compared with American women. However, recent animal, clinical, and gene expression studies provide evidence against its preventive role in breast cancer (32,33). Our BRET assay shows that genistein induces ER␣ homodimerization at 100 nM, a physiological concentration easily achievable by dietary intake (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent animal, clinical, and gene expression studies provide evidence against its preventive role in breast cancer (32,33). Our BRET assay shows that genistein induces ER␣ homodimerization at 100 nM, a physiological concentration easily achievable by dietary intake (32)(33)(34)(35). Because ER␤ expression is lost in highly aggressive tumors, the concomitant activity of genistein to induce ER␣ homodimerization and subsequently activate ER␣-mediated transcription (36) may explain the failure of genistein in clinical trails for the treatment of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…18) However, hyperdoses of isoflavones have been suggested to induce breast cancer. 19,20) It has been reported that circulating estrogen levels are positively associated with breast cancer risk. 21) In the present study, EBNE ingestion did not affect the serum estradiol concentration (Table 2).…”
Section: Improvement Of Bone Strength and Dermal Thickness Due To Diementioning
confidence: 99%
“…Proposed anticancer mechanisms of action include modulation of estrogen receptor (ER) signaling as a partial agonist of ERα and β (6), downregulation of protein kinases and DNA topoisomerase (7), induction of early mammary cell differentiation (8), inhibition of angiogenesis (9), and modulation of intracellular enzyme activities (10). However, a few reports have shown that genistein can also increase proliferation of breast cancer cells in vitro and in ovariectomized rodent models of breast cancer (11)(12)(13)(14), suggesting the effects of genistein on the breast cancer cell growth may be multifaceted.…”
Section: Introductionmentioning
confidence: 99%